An assessment of the implementation of the Service Delivery Improvement Policy in the Department of Arts, Culture and Tourism in KZN - Mnculwane, Vikinduku Victor (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009.